Pendekatan Balance Scorecard Dalam Menganalisis Pengukuran Kinerja Bank Negara Indonesia (Persero) Tbk - Putri Adelia Siregar; Hwihanus Hwihanus (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This research seeks to assess PT. BNI (Persero) Tbk's performance through the utilization of the balanced scorecard approach, encompassing financial, customer, internal processes, and learning/growth perspectives. The study, employing a descriptive method, focuses on PT. BNI (Persero) as the sample population, utilizing documentation techniques for data collection. Results indicate favorable financial indicators (ROA, ROE, NPM, BOPO, LDR), subpar customer metrics (customer acquisition, retention), excellent internal business processes (AETR, NGR), and positive learning/growth aspects (employee productivity, ETTE).